2012
DOI: 10.1007/s00464-011-2139-6
|View full text |Cite
|
Sign up to set email alerts
|

Hysteroscopic placement of tubal sterilization implants: virtual reality simulator training

Abstract: We established face and construct validity for EssureSim, an educational VR simulator for hysteroscopic tubal sterilization implant placement. The next steps are to investigate convergent and predictive validity to affirm the real capacity of transferring the skills learned on the training simulator to the patient in the operating room.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…We considered a 20 % reduction in intervention time as a relevant difference. This resulted in a minimum number of 12 subjects in each group, which is in line with previously reported validation studies using similar set‐ups [5, 6, 10, 17–19, 24–27, 31, 33, 34, 36]. Sixteen experts, 19 intermediates, and 33 novices were finally recruited at the training course.…”
Section: Methodssupporting
confidence: 61%
“…We considered a 20 % reduction in intervention time as a relevant difference. This resulted in a minimum number of 12 subjects in each group, which is in line with previously reported validation studies using similar set‐ups [5, 6, 10, 17–19, 24–27, 31, 33, 34, 36]. Sixteen experts, 19 intermediates, and 33 novices were finally recruited at the training course.…”
Section: Methodssupporting
confidence: 61%
“…In this manner, realism was evaluated Not all performance parameters measured by the simulator were able to differentiate between participants with varying hysteroscopy experience. We hereby confirm findings of previous studies by Bajka et al [30] and Panel et al [34], who investigated the face and construct validity of the diagnostic and sterilization module on this hysteroscopy simulator, respectively. Both studies found that less than half of all used parameters significantly correlated with hysteroscopy experience.…”
Section: Discussionsupporting
confidence: 91%
“…Such simulators are already in use in various medical specialties like ophthalmology, gynaecology and laparoscopic surgery. 19,20,21 Next to their advantage as teaching aids, they can be used as a tool for quality control before the performance of a specific procedure. These simulations can be enriched by means of augmented or virtual reality.…”
Section: Future Considerationsmentioning
confidence: 99%